1980
DOI: 10.1002/art.1780231007
|View full text |Cite
|
Sign up to set email alerts
|

Cell cultures from bone affected by pacet's disease

Abstract: Cells obtained from Paget's bone specimens were maintained in culture for up to 8½ months. The cells had several characteristics of bone cells including the presence of alkaline phosphatase, acid phosphatase, or succinic dehydrogenase as demonstrated histochemically. Electron microscopy revealed nuclear inclusions similar to those found in the osteoclasts of Paget's disease in 4 of 11 cultures. Immunohistology utilizing specific antisera demonstrated the presence of respiratory syncytial virus antigen(s) in 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…Doubling times were similar to those found by others using this technique: 5 days [6] and 4-12 days [10,11]. The mean doubling times among the three groups of subjects were very similar.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Doubling times were similar to those found by others using this technique: 5 days [6] and 4-12 days [10,11]. The mean doubling times among the three groups of subjects were very similar.…”
Section: Discussionsupporting
confidence: 87%
“…This technique has not been widely used in the study of metabolic bone disease. However, over the past several years it has been used to study patients with Paget's disease [10], diseases of skeletal development [11], renal osteodystrophy [12] and pseudohypoparathyroidism [13,14]. Recently we [1] and others [15][16][17][18] have applied the explant technique to derive osteobtast-like cells from osteoporotic patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, these patients do not have high titers of circulating measles antibodies when compared with control subjects [49]. In the same disease, respiratory syncytial virus antigens were reported in cultured bone cells [36]. As for inclusion-body myositis, further studies are needed to sustain these viral hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Rebel et al (1980) have demonstrated such antigens from measles virus using both immunofluorescence and immunoperoxidase (Heyderman 1979) techniques. Using similar methodology, Mills et al (1980) have demonstrated similar antigens from RSV and, more recently, elements of both viruses (Mills et al 1984) ! Basle et al (1983) have also identified 4 of 6 structural measles antigens in Pagetic osteoclasts, using a monoclonal antibody technique, and emphasized the absence of two antigens associated with viral replication; the significance of this is discussed later.…”
Section: Introductionmentioning
confidence: 95%